Deeper writing : quick writes and mentor texts to illuminate new possibilities - Holland, Robin W. (Corwin, a SAGE Company, 2013)
Your best tool for building fluent writers Make your classroom's writing time really count, with smart and compelling texts designed to enhance the instruction you're already providing. Whether you teach 4th grade, 12th, or anything in between, you'll foster authentic writing every day, building fluency and teaching students to write for a variety of purposes-top priorities in the Common Core. Look for: 45 quick writes in an easy-to-use framework with suggested grade levels Carefully selected mentor texts that provide models and inspiration Guidelines for crafting your own quick wr.